HUBUNGAN KOORDINASI MATA DAN TANGAN TERHADAP KEMAMPUAN SERVIS ATAS TIM BOLA VOLI PUTRA SMK PGRI PEKANBARU - Ahmad Fadilah; Aref Vai; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Based on the author's direct observations or observations on the Men's Volleyball Team at SMK PGRI Pekanbaru, it can be seen that the service ability for the Men's Volleyball Team has not been maximized, especially when carrying out the upper service ability training in the game is still not optimal, such as the number of balls that cannot pass as well as getting stuck in the net when the player serves over and there are still many who cannot direct the ball when serving to an empty place and the ball is still easy for the opposing player to receive the serve ball. The purpose of this study was carried out using a correlational design which aims to investigate how far the variables in one factor are related to other factors. Correlation is a study designed to determine the level of relationship between variables in a population and aims to determine how much the contribution between the independent variable and the dependent variable is. The population in this study was the Men's Volleyball Team at SMK PGRI Pekanbaru who were registered as 24 students. In this study the sampling technique that will be used is purposive sampling, namely the sampling technique used by researchers if they have certain considerations in taking the sample, (Arikunto 2010: 97). In this study, due to the small population, the men's volleyball team at SMK PGRI Pekanbaru was used as the sample. Based on the research results and data processing using research statistical procedures, it was concluded that there was a 95% confidence level relationship between eye and hand coordination on the results of top serve with a value of rxy = 0.972 greater than rtable = 0.404. So it can be concluded rcount> rtable (Related) so that Ho is rejected and Ha is accepted.Key Words: Eye and Hand Coordination Relationship, Top Service